Serum Cytokine Levels and Anxiety and Depression Rates in Patients with Alopecia Areata - Ataseven, Arzu; Saral, Yunus; Godekmerdan, Ahmet (Aves, 2011)
Objective: Alopecia areata (AA) is a disease characterized by patchy hair loss. Although the etiopathogenesis of AA is still unclear, it has been hypothesized that immune system dysfunction and stress are involved. The aim of this study was to evaluate possible associations between AA and depression, anxiety and serum levels of cytokines interleukin (IL)-1 beta, IL-6, IL-8 and IL-10. Materials and Methods: Forty-three patients who were diagnosed with AA were prospectively enrolled into the study. Thirty age-and sex-matched healthy individuals were included as the control group. The Hamilton Rating Scale for Depression and the Hamilton Rating Scale for Anxiety were used. For children between the ages of 7 and 16, the Children's Depression Inventories was completed. Serum levels of the cytokines IL-1 beta, IL-6, IL-8, and IL-10 were analyzed by ELISA. Results: No significant differences were observed between patients and controls with respect to serum cytokine levels (p>0.05). Depression rates were found to be 50% and 30% in AA patients and controls, respectively (p<0.05). Similarly, anxiety rates were found to be 63% and 23.3% in AA patients and controls, respectively (p<0.05). Conclusion: Depression and anxiety were found more frequent in AA patients than healthy individuals. Therefore, when considering management therapy, an entire psychiatric evaluation should also be performed. However, no differences were found in serum cytokine levels of patients and controls.
Keywords: Alopecia areata; Depression; Anxiety; Cytokines